Building rich Internet apps with Open Data Protocol. - Burgess, Shayne
Windows Azure.
Keywords: Microsoft SharePoint (Electronic resource); Rich Internet Application (RIA).; Open Data Protocol (OData).; Windows Communication Foundation (WCF).; Entity Framework (EF).; ADO.NET.